Breeding in Alstroemeria in Argentina: obtaining hybrids through em- bryo rescue. - PAKOCA, C. (Universidad Nacional del Litoral, 2021)
The Alstroemeria genus comprises about 90 species restricted to South America, 10 species are distributed in Argentina. Its cultivation has grown in popularity due to the variety of colors and post-harvest quality of its ﬂowers. The objective of this work was the study of the compatibility between A. psittacina and 9 alstroemeria varieties and the adjustment of the embryo rescue technique. The study of the growth of the pollen tube allowed to detect different situations according to the varieties. The number of germinated embryos and the obtaining of normal seedlings varied with respect to the variety and time to rescue. In the case of crosses with “Belvedere”, the highest number of germinated embryos was produced at 14 days post pollination (DPP), for “Cartagena” at 7 DPP and for “Costa Azul”, no signiﬁcant differences were detected between both times. Seedlings were obtained in the crosses with “Belvedere”, “Cartagena”, “Costa Azul”, “Himalaya” and “Virginia”. The highest reproductive efﬁciency was in “Costa Azul” being 6,6 and 8,4 for rescues at 7 and 14 DPP, respectively. These results will allow the advancement of the Alstroemeria breeding program to obtain Argentine varieties.